1981
DOI: 10.1007/bf02534969
|View full text |Cite
|
Sign up to set email alerts
|

Lack of specificity in accumulation of sterols byPhytophthora cactorum

Abstract: The kinetics of sterol uptake in Phytophthora cactorum were examined. A Vma x of 4.81 X 10 -s ~tmol/min/mg dry wt and an average apparent Km of 18.0 t~M were determined for both cholesterol and sitosterol accumulation. Selectivity for specific sterols was not apparent in the accumulation, esterification, or distribution of sterols by Phytophthora cactorum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…The interaction between light and cholesterol supplementation observed in this species by Hendrix (1967) is consistent with the hypothesis that sterol uptake in the mycelial phase is restricted. However, this is in contrast with the results obtained with Phytophthora cactorum Gonzales & Parks (1981), who observed that cholesterol was accumulated by the mycelia grown in liquid culture when the sterol was offered. Differences in sterol absorption from liquid as opposed to agar cultures have been observed (Nes et al, 1983;Nes & Stafford, 1983) but did not appear to contribute to the differences noted in our results.…”
Section: Discussioncontrasting
confidence: 99%
“…The interaction between light and cholesterol supplementation observed in this species by Hendrix (1967) is consistent with the hypothesis that sterol uptake in the mycelial phase is restricted. However, this is in contrast with the results obtained with Phytophthora cactorum Gonzales & Parks (1981), who observed that cholesterol was accumulated by the mycelia grown in liquid culture when the sterol was offered. Differences in sterol absorption from liquid as opposed to agar cultures have been observed (Nes et al, 1983;Nes & Stafford, 1983) but did not appear to contribute to the differences noted in our results.…”
Section: Discussioncontrasting
confidence: 99%
“…The genus Phytophthora and other members of the oomycete order Peronosporales are sterol auxotrophs (Nes, 1987). They lack sterol biosynthetic activity and accumulate sterols available from their environment in their membranes (Gonzales and Parks, 1981). The nutritional dependence on external sterol supplies is expected to make Phytophthora especially vulnerable to perturbation by sterol-binding proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that most oomycetes cannot synthesize their own sterols for their growth and reproduction and hence are sterol auxotrophs led to the proposition that oomycetes secrete elicitins to bind and sequester sterols from the host plant and shuttle these sterols back to meet their own demand (Dahlin et al, 2017;Gonzales & Parks, 1981;Ponchet et al, 1999).…”
Section: Oomyce Te S Are S Terol Auxotroph S and S En S Itive To The ...mentioning
confidence: 99%